Penggunaan Cyber Warfare dalam Konflik Bersenjata Internasional Antara Rusia-Ukraina Menurut Hukum Humaniter Internasional - Andyta Sekar Pratiwi; Syofirman Syofyan; Mardenis Mardenis (Fakultas Hukum Universitas Andalas, 2023)
Today's the advancements of technology have an impact on many aspects of life, including health, education, transportation, business, information communication, and government administration. Nonetheless, given the strong relationship between technology and the military, technology advancements could lead to a war. The sheer proliferation of technologies implemented in military operations spawned technology-based warfare called cyber warfare. Cyber warfare refers to wars carried out through the virtual world and is coordinated with conventional warfare. In cyber warfare, opposing countries perform cyber operations through cyberspace as the latest weapon of warfare launched to destabilize the national security and stability of the target state. The current cyber warfare is in the international armed conflict between Russia and Ukraine. This article analyses the deployment of cyber warfare in international armed conflict from the international humanitarian law perspective, and it also investigates Russia's use of cyber warfare against Ukraine. The purpose of this article is to understand how international humanitarian law rules the use of cyber warfare in international armed conflicts, in addition to the way Russia employs cyber warfare against Ukraine. This article is normative law research which uses the statute approach with juridical-normative research method. The findings found that cyber warfare carried out within the framework of international armed conflict is subject to international humanitarian law and that its use is also restricted by the fundamental principles of international humanitarian law. The research also found that Russia's cyber warfare against Ukraine in an international armed conflict is against the principles of differentiation and proportionality.